After Contemporary Art: Actualization and Anachrony - Karlholm, Dan (The Nordic Journal of Aesthetics, 2017)
Departing from a critical assessment of the most widespread and initiated definitions of Contemporary Art from the last decade and a half, sustaining a world-wide discourse on contemporary art and contemporaneity, this article will deal with two aspects of an immodest proposal captured by the keywords actualization and anachrony. While current discussions on contemporary art are arguably reproducing modernist assumptions on the primacy of innovation, bolstered by a veiled avant-garde logic, the proposal to regard contemporary art as actualized art upsets not only ideas on what art after postmodernism might mean, but the whole edifice of historicist historiography. An anachronic perspective, a bi- or polychronic situatedness of the work of art, could be used to liberate art from being defined according to its unique descent, and to embrace, instead, a chronologic open to art’s continuous “life” through its successive aesthetic accessions and actualizations in time.